Neo-Thomism and Evolutionary Biology: Arintero and Donat on Darwin - Recio, Gonzalo Luis (Religions, 2024)
Pope Leo XIII’s publication of Aeterni Patris (1879) was a major factor in the great revival of Thomistic thought in the late 19th and the first half of the 20th centuries. Among the authors that took up the challenge implicit in the Pope’s document of bringing Aquinas and his thought into the intellectual debates of the times we find two interesting proposals. The first is that of Juan González Arintero, a Spanish Dominican, and the second one is that of Josef Donat, a Jesuit born and raised in the Austrian Empire. Arintero is mostly known in Catholic circles for his influential works on mysticism, but in fact he devoted much of his early work to the subject of evolution, and how it could interact with the Catholic faith in general, and with Thomism in particular. Donat is the author of a Summa Philosophiae Christianae, a collection that was widely read in Catholic seminaries well into the 20th century. In this paper we will focus on the differing ways in which these authors tackled the problems and questions presented by Darwinian evolutionism to the post-Aeterni Patris Thomism.